Maori and Pasifika higher education horizons - Cram, Fiona (Diversity in higher education ;, 2014)
Rarely have Pasifika writers come together to share their experiences in this field. Focusing on the past, current and future status and success of Maori and Pasifika peoples in tertiary education within Aotearoa New Zealand, this volume covers diverse issues from the countries colonial history, to student engagement with new technology.